WHY DO PEOPLE SEE A FINANCIAL SYSTEM AS A WHOLE VERY IMPORTANT? - Masyita, Dian (Journal of Islamic Monetary Economics and Finance, 2015)
The action of one person will affect the others and then the action of one country will affect other countries. Financial crisis is like a contagious disease, which spreads everywhere. The failure in capturing systemic risk is the interconnected market events (’network externalities’) can produce self-reinforcing cycles then create the harmful situation. What happened in the banking regulation particularly Basel II? In reality, Basel II did not work completely in 2008. Since the implementation of risk management based on Basel II has been a prerequisite for a bank, it is supposed to make a positive impact. Misplaced reliance on mathematical model and statistics in managing risk could one of the problems in the decision making process. Using system thinking, system dynamics paradigm and theory of feedback system, this paper tries to see the risk management from different perspective and to enrich the understanding of how financial systems work: what drives them and causes the behavior. Many lessons can be learnt from this financial contagion since Islamic banking and finance system has inevitably been a part of the international financial systems.